2016
DOI: 10.3109/10641963.2016.1148159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral appliance therapy on blood pressure in Japanese patients with obstructive sleep apnea

Abstract: A certain time period of OA therapy effected BP reduction in mild to moderate OSA patients without cardiac and/or cerebrovascular diseases. Its antihypertensive effect was greater in OSA patients whose BP was higher before receiving OA therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Blood pressure is reduced from MAD treatment compared with placebo and mostly to a similar degree as with CPAP in the relatively small samples studied [5,9,11]. The blood pressure effects are particularly evident at night-time, in hypertensive patients and probably among females [18,[42][43][44][45][46][47]. Sex differences in effects from OSA treatments are mainly unknown, since mixed samples have included a majority of males (80% on average).…”
Section: Blood Pressure and Cardiovascular Healthmentioning
confidence: 99%
“…Blood pressure is reduced from MAD treatment compared with placebo and mostly to a similar degree as with CPAP in the relatively small samples studied [5,9,11]. The blood pressure effects are particularly evident at night-time, in hypertensive patients and probably among females [18,[42][43][44][45][46][47]. Sex differences in effects from OSA treatments are mainly unknown, since mixed samples have included a majority of males (80% on average).…”
Section: Blood Pressure and Cardiovascular Healthmentioning
confidence: 99%
“…20,21 Gotsopoulos et al 20 revealed a significant reduction with the 4 weeks of oral appliance therapy in mean 24hour diastolic blood pressure (1.8 6 0.5 mm Hg) compared with the control (P = .001) but not in 24-hour systolic blood pressure. 20 Sekizuka et al 21 25 revealed daytime and nighttime SBP predicted all-cause and cardiovascular mortality, coronary heart disease, and stroke. Since it is still controversial whether nighttime or daytime BP can be a better prognostic factor for cardiovascular diseases, we calculated both nighttime and daytime BP preoperatively and postoperatively.…”
Section: Discussionmentioning
confidence: 97%
“…20,21 Gotsopoulos et al 20 revealed a significant reduction with the 4 weeks of oral appliance therapy in mean 24-hour diastolic blood pressure (1.8 ± 0.5 mm Hg) compared with the control ( P = .001) but not in 24-hour systolic blood pressure. 20 Sekizuka et al 21 demonstrated 237 Japanese patients with mild to moderate OSA with 8 to 12 weeks of oral appliance therapy. The antihypertensive effect of oral appliance therapy resulted in systolic BP of −2.4 ± 14.8 ( P = .078) and diastolic BP of −2.0 ± 11.7 mm Hg ( P = .045) in all patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…After consensus meetings, the reviewers agreed on the methodological quality of all articles. Nine articles were considered of low [37][38][39][40][41][42][43][44][45] and 16 articles of sufficient [46][47][48][49][50] methodological quality, including 11 RCTs (n=719 patients) [51][52][53][54][55][56][57][58][59][60][61] (Table 1 shows the study characteristics of articles with sufficient methodological quality).…”
Section: Resultsmentioning
confidence: 99%